The shape of water - Toro, Guillermo del, 1964-; Taylor, Vanessa, 1978-; Dale, J. Miles; Hawkins, Sally, 1976-; Spencer, Octavia; Shannon, Michael, 1974-; Jenkins, Richard, 1947-; Jones, Doug, 1960-; Stuhlbarg, Michael; Sequeira, Luis; Desplat, Alexandre; Wolinsky, Sidney; et al. (Beverly Hills, California : Twentieth Century Fox Home Entertainment, 2018)
An otherworldly fairy tale, set against the backdrop of Cold War-era America circa 1962. In the hidden high-security government laboratory where she works, lonely Elisa is trapped in a life of isolation. Elisa's life is changed forever when she and co-worker Zelda discover a secret classified experiment.
Originally released as a motion picture in 2017.
Special features: A fairy tale for troubled times; theatrical trailers.
Costume designer, Luis Sequeira ; music, Alexandre Desplat ; film editor, Sidney Wolinsky ; production designer, Paul Austerberry ; director of photography, Dan Laustsen.
Sally Hawkins, Octavia Spencer, Michael Shannon, Richard Jenkins, Doug Jones, Michael Stuhlbarg.
MPAA rating: R; sexual content, graphic nudity, violence and language CHV rating: 14A.
DVD, NTSC region 1, widescreen (1.85:1) presentation; Dolby Digital 5.1, Dolby Digital 2.0.
Keywords: Laboratories -- Drama; Security classification (Government documents) -- Drama; Science -- Experiments -- Drama; Fairy tales -- Drama; Cold War -- Drama; Mermen -- Drama; Amphibians as laboratory animals -- Drama; Orphans -- Drama; Mute persons -- Drama; Animals, Mythical -- Drama; Thrillers (Motion pictures); Feature films; Fiction films; Romance films; Fantasy films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities